Expression and prognostic significance of VEGF and mTOR pathway proteins in metastatic renal cell carcinoma patients: a prognostic immunohistochemical profile for kidney cancer patients - Liontos, M.; Trigka, E.-A.; P Korkolopoulou; Tzannis, K.; Lainakis, G.; Koutsoukos, K.; Kostouros, E.; Lykka, M.; Papandreou, C.N.; Karavasilis, V.; Christodoulou, C.; Papatsoris, A.; et al. (World Journal of Urology, 2016)
Purpose: To identify prognostic molecular profiles in patients with mRCC treated with sunitinib, we performed immunohistochemical analysis for VEGF and PI3K/Akt/mTOR pathway components. Methods: The immunohistochemical expression of VEGF, p85α, p110γ, PTEN, p-Akt, p-mTOR, p-4E-BP1 and p-p70S6K was studied in 79 patients with mRCC who received first-line treatment with sunitinib. Expression was correlated with clinicopathological features and survival. Results: VEGF was highly expressed (median H-Score 150), while positivity for the markers of the PI3K/Akt/mTOR pathway was: p85α 43/66 (65 %), p110γ41/60 (68 %), PTEN 32/64 (50 %), p-Akt57/63 (90 %), p-mTOR48/64 (75 %), p-4E-BP1 58/64 (90 %) and p-p70S6K 60/65 (92 %). No single immunohistochemical marker was found to have prognostic significance. Instead, the combination of increased p-mTOR and low VEGF expression was adversely correlated with overall survival (OS) (3.2 vs. 16.9 months, P = 0.001). Conclusion: Immunohistochemistry for VEGF and p-mTOR proteins may discriminate patients refractory to first-line sunitinib with poor prognosis. Prospective validation of our findings is needed. © 2016 Springer-Verlag Berlin Heidelberg
Keywords: mRCC; mTOR; Sunitinib; VEGF